Factors Affecting Mental Health Among Chinese College Students: A Preliminary Review of Literature - Feng, Lei; Ellen, Chung; Ling Siew, Eng (UNIMAS Publisher, 2022)
Mental health has attracted much attention over the past decades. Academic pressure, employment pressure, interpersonal relationship, emotional problems all impact students' bodies and minds. This paper aims to comb through relevant literature to identify the factors affecting mental health among college students in China. Five hundred forty-five articles were retrieved containing relevant keywords such as factors affecting mental health from the China National Knowledge Infrastructure (CNKI) database. These articles were published from 1989 to the first half of 2021. A broad thematic analysis revealed that these factors could be grouped into four main categories: family, social, college-life, and individual factors. This paper has a significant contribution as it lays the foundation for further investigation into mental health issues among college students in China.